Strategi Pemasaran Digital Menggunakan Media Sosial Tiktok untuk Meningkatkan Minat Beli UMKM - Winda Riani; Siti Nurkhodijah; Puput Syahrani; Tiara Olivia; Nadia Putri; Aisyah Lestari; Junaidy Junaidy; Trysanti Kisria Darsih (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The rapid advancement of digital technology has fundamentally changed the marketing practices of MSMEs in Indonesia. TikTok, as a short-video-based social media platform, is increasingly recognized as a strategic medium for expanding market reach and stimulating consumer purchase intention. This study was designed to systematically investigate the implementation of TikTok-based digital marketing strategies in supporting the growth and sustainability of MSMEs. A descriptive qualitative approach was applied, with data collection techniques including in-depth interviews with five MSME managers as key informants, content observation, documentation, and online surveys of consumers exposed to promotional content. The findings revealed that TikTok features such as live streaming, hashtag challenges, and collaboration with creators effectively increase consumer engagement, build brand awareness, and stimulate purchase intention. However, MSMEs face challenges such as limited human resources and algorithm understanding. This study concludes that TikTok has great potential as a digital marketing medium for MSMEs, provided that creative, consistent, and consumer-oriented content strategies are optimally implemented.